2015
DOI: 10.5194/bg-12-3655-2015
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture influence on the interannual variation in temperature sensitivity of soil organic carbon mineralization in the Loess Plateau

Abstract: Abstract. Temperature sensitivity of soil organic carbon (SOC) mineralization (i.e., Q 10 ) determines how strong the feedback from global warming may be on the atmospheric CO 2 concentration; thus, understanding the factors influencing the interannual variation in Q 10 is important for accurately estimating local soil carbon cycle. In situ SOC mineralization rate was measured using an automated CO 2 flux system (Li-8100) in long-term bare fallow soil in the Loess Plateau (35 • 12 N, 107 • 40 E) in Changwu, Sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…Changes in both the distribution and amount of precipitation have significant effects on soil CO 2 emissions by regulating VWC; this is especially true in rain-fed agricultural areas, where precipitation is the primary driver of biological activity [ 26 ]. Generally, an increase in VWC will increase the aboveground and underground biomass, as well as substrate concentrations of plants [ 5 , 13 ], thereby enhancing R s [ 14 ]. However, a previous study also found that a decrease in VWC increased T s and then increased R s [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Changes in both the distribution and amount of precipitation have significant effects on soil CO 2 emissions by regulating VWC; this is especially true in rain-fed agricultural areas, where precipitation is the primary driver of biological activity [ 26 ]. Generally, an increase in VWC will increase the aboveground and underground biomass, as well as substrate concentrations of plants [ 5 , 13 ], thereby enhancing R s [ 14 ]. However, a previous study also found that a decrease in VWC increased T s and then increased R s [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The R s was fitted to T s and VWC with empirical exponential and quadratic functions [ 10 , 13 ], respectively: where R s , VWC, and T s represent the soil respiration, soil volume water content, and soil temperature, respectively, and a, b, and c are fitting coefficients. Then, the following nonlinear models were used to express the relationships between VWC and T s and R s [ 31 , 32 ]: …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Soil-based techniques, however, are not suited for Mediterranean areas. In these environments, seasonal variability of both soil moisture and temperature is a serious constraint for accurate forecast of the actual amounts of mineral N available to plants since mineralization rates are greatly affected by these two parameters (Pessarakli, 1994;Zhang et al, 2015). Among plant-based approaches, the critical N concentration (N ct expressed as % of Dry Matter, DM) has been proven to be a reliable parameter for monitoring N fertilization rates in the soil-plant system (Lemaire et al, 2007).…”
Section: Introductionmentioning
confidence: 99%